Physical Activity Promotion in a Safety-Net Clinic: Does the Provider Make a Difference? A Pilot Study. Issue 4 (2021) - Bowen, Pamela G.; Opoku-Agyeman, William; Affuso, Olivia; Levi, Paula; Wingo, Nancy
ABSTRACT: Background: Despite the long-term health benefits of physical activity, many Americans across the life span do not meet the recommended levels. However, physical activity discussions in the clinic setting may hold promise. The purpose of this study aimed to understand health care providers' beliefs and practices about physical activity discussions being a part of patients' health care treatment. Methods: Semistructured, audiotaped interviews were conducted to elicit narratives from 10 health care providers. Interview data were transcribed verbatim, and then coded and analyzed by two qualitative researchers using NVivo12. Results: Three major themes emerged were as follows: importance of regular physical activity counseling for vulnerable populations; patients' lack of regular physical activity, including subthemes of lack of time, current health conditions, and social determinants of health; and health care provider's reflections about their own physical activity. Conclusions: Health care providers have an important role when it comes to promoting good health. Having physical activity discussions with patients at every clinic visit is a great opportunity to encourage patients to engage in healthy lifestyle behaviors such as regular physical activity. From this pilot study, implications for practice may include increased awareness of the health care providers to discuss physical activity at every visit, which may lead to improved provider–patient communications related to the benefits of daily physical activity behaviors. These discussions may even have a secondary gain of encouraging the providers themselves to adopt the healthy behavior and thereby serve as a role model for their patients.